Efektivitas Penerapan Remedial Teaching Terhadap Peningkatan Kemampuan Siswa Dalam Memahami Pelajaran - Lailatus Sururiyah (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2018)
Remedial teaching is a teaching of improvement in the school curriculum system. There is also a call by the term corrective instruction. This refinement teaching is a complement to the overall teaching process. Teaching this improvement needs to be mastered at least known by the teacher of the subject or the lecturer at the school. Remedial teaching is a form of teaching that is healing or corrective. Or with a brief teaching that makes it good. Educational services provided to learners to improve their learning achievements so as to achieve defined completeness criteria and activities aimed at helping students who have difficulty in mastering the subject matter. Remedial teaching aims to enable students to achieve the learning objectives that have been set at least in accordance with the minimum degree of mastery. Found bahwasannya Learners have the ability and characteristics yamg different. In accordance with the abilities and different characteristics of the problem is faced pesrta different also. In carrying out the learning, an educator needs to respond to the difficulties encountered and the advantages possessed by learners. In essence all learners will be able to achieve the standard conferences specified, only the time achievement is different. There are slow learners in the mastery of a material and there are also very fast learners in the mastery of the material. If there is a learner who does not reach a predetermined competency, then the school performs an action that is the remedial learning program or improvement. Remedial is required for learners who have not achieved the minimum capability set out in the lesson plan. The provision of remedial learning programs is based on the background that educators need to pay attention to individual differences in learners. Remedial teaching thus plays an important role in improving the ability of students in understanding the lesson.Kata Kunci: Remedial Teaching, Peningkatan Kemampuan, Siswa, Pelajaran